2014
DOI: 10.1249/mss.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Aerobic Function in Patients with Cystic Fibrosis during Ramp Exercise

Abstract: Young patients with mild-to-moderate CF present with impaired aerobic function during ramp incremental cycling exercise. Because the rate of fractional O2 extraction during ramp cycling exercise was not altered by CF, yet SpO2 was lower, the present findings support the notion of centrally mediated oxygen delivery to principally limit the aerobic function of pediatric patients with CF during ramp incremental cycling exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 31 publications
(54 reference statements)
1
27
1
Order By: Relevance
“…Despite positive correlations with V̇O 2max , no mean differences in OUES were observed between CF and CON at each parameter (of intensity, time, and metabolic thresholds)—a finding contrasting previous adult and pediatric studies assessing OUES in independent groups . However, it could be argued that as a significantly lower V̇O 2max was not observed in CF versus CON in the present study, in contrast to previous findings, a recruitment bias may be present. The lack of differences between groups may be due to deconditioning of control participants (as opposed to increased fitness in CF), with V̇O 2max being 10 mL kg −1 min −1 lower in the current study, when compared to previous research .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite positive correlations with V̇O 2max , no mean differences in OUES were observed between CF and CON at each parameter (of intensity, time, and metabolic thresholds)—a finding contrasting previous adult and pediatric studies assessing OUES in independent groups . However, it could be argued that as a significantly lower V̇O 2max was not observed in CF versus CON in the present study, in contrast to previous findings, a recruitment bias may be present. The lack of differences between groups may be due to deconditioning of control participants (as opposed to increased fitness in CF), with V̇O 2max being 10 mL kg −1 min −1 lower in the current study, when compared to previous research .…”
Section: Discussioncontrasting
confidence: 99%
“…First, utilizing CPET time to exhaustion (TTE) as a measure of intensity may be flawed, as it does not account for variances in individual metabolic thresholds. As the presence of reduced maximal capacity and an altered oxygen cost of exercise have been demonstrated in individuals with CF, it is conceivable that patients in this previous study may be exercising at differing relative exercise intensities (ie, as a percentage of V̇O 2max ), and even within differing intensity domains, despite being matched for exercise duration. Second, there was a lack of appropriate normalization for the influence of body size, with authors utilizing ratio‐standard scaling, whereas previous research has shown this to be insufficient at removing residual effects of body size from OUES …”
Section: Introductionmentioning
confidence: 95%
“…In support, Saynor et al . () found no evidence for impaired peripheral oxygen extraction in adolescents with CF in a comparable study population. However, this could still differ between patients with different levels of disease severity and co‐morbidities.…”
Section: Discussionmentioning
confidence: 79%
“…For example, Bongers et al ,29 in a group of 22 children with CF, found Vo 2peak to be significantly lower than healthy controls and Saynor et al 30 found a reduced aerobic capacity (mean Vo 2peak 36.3 mL/kg/min) in those with CF compared with controls.…”
Section: Discussionmentioning
confidence: 97%